REVOLUTION OF 1917-1921 IN THE HISTORICAL MEMORY OF UKRAINE: REGIONAL DIMENSION - Repeta, I. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2018)
At the present stage of Ukraine's development, one of the decisive factors that significantly influences the processes of state-building of the Ukrainian nation is historical memory, which is an important component of the self-identification of the population. This article covers the factors that influenced the formation of historical memory in the regions of the country, one of which is the revolutionary events of 1917-1921.